Night train - Snijders, A. L. (New Directions paperbook, 2021)
"Gorgeously translated by Lydia Davis, the miniature stories of A. L. Snijders might concern a lost shoe, a visit with a bat, fears of travel, a dream of a man who has lost a glass eye: uniting them is their concision and their vivacity. Lydia Davis in her introduction delves into her fascination with the pleasures and challenges of translating from a language relatively new to her. She also extolls Snijders's "straightforward approach to storytelling, his modesty and his thoughtfulness." Selected from many hundreds in the original Dutch, the stories gathered here-humorous, or bizarre, or comfortingly homely-are something like day-book entries, novels-in-brief, philosophical meditations, or events recreated from life, but-inhabiting the borderland between fiction and reality-might best be described as autobiographical mini-fables"--